CYBERBULLYING YOUTH ON SOCIAL MEDIA - M. Jorgie Arroyandy; Sandro Saragi; Muhammad Akbar; M Iqbal Andriano Bengkulah; Jimi Mardiansyah; Muhammad Naufal Luthfi; Mahesa Belanti; Siti Fatimah; Bayu Sefryian Saputra (CV. Doki Course and Training, 2023)
The purpose of this study is to analyze how often perpetrators carry out cyberbullying actions. The type of research used is a type of survey. Respondents resulting from the survey amounted to N = 58 who were determined using data collection carried out by distributing online questionnaires through the Google form. Meanwhile, this study used the Mixed Method method with a sequential explanatory design. The results of this study can be concluded that most cyberbullying perpetrators have carried out cyberbullying and the majority are involved in low-level cyberbullying with an age range of 17-18 years.